2023
DOI: 10.13073/fpj-d-22-00060
|View full text |Cite
|
Sign up to set email alerts
|

Borate Treatment of CLT Panels Using Vacuum: A Proof of Concept

Abstract: Cross-laminated timber (CLT) is an increasingly popular wood-based alternative for large building applications. CLT panels are typically not treated due in part to a perceived lack of efficient and effective methods for treating large panels and a lack of information on what effect treatment processes may have on the panels' mechanical properties. We propose that treating CLT panels with borate solution, applied under vacuum in flexible bags, could provide a practical and effective option for providing preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Non-pressure treatments (Miyauchi et al 2021) and the use of exterior coatings (Bobadilha et al 2020) are becoming relevant options while mainly borate treatments have been checked on their potential (Lloyd et al 2019, Taylor et al 2023, Bagheri et al 2022.…”
Section: Wood Preservationmentioning
confidence: 99%
“…Non-pressure treatments (Miyauchi et al 2021) and the use of exterior coatings (Bobadilha et al 2020) are becoming relevant options while mainly borate treatments have been checked on their potential (Lloyd et al 2019, Taylor et al 2023, Bagheri et al 2022.…”
Section: Wood Preservationmentioning
confidence: 99%
“…However, another study showed that BA treatment enhances properties such as the surface roughness, modulus of elasticity (MOE), and density of wood (Simsek et al, 2010). A study by Taylor et al (2023), concluded that vacuum treating CLT panels with borate provides sufficient levels of preservative retention and has minimal effects on mechanical properties. From the studies mentioned, the lack of systematic approaches to enhance the physical and mechanical properties of timber products limits boron compounds' commercial viability.…”
Section: Introductionmentioning
confidence: 99%